Assessment of Adequacy of Haemodialysis by Urea Kinetic Modeling (UKM) (Jalalabad Medical Journal, 2026)
Dialysis adequacy is an important parameter with regards to morbidity and mortality in chronic haemodialysis (HD) patients. Measuring the adequacy of HD is not an easy task. There is no objective, reliable and universally accepted criteria for measuring the adequacy. Clinically, several parameters must be considered to provide adequate dialysis, such as control of fluid overload and electrolytes disturbance, correction of metabolic acidosis and dialysis dose. This cross-sectional study explores the assessment of the adequacy of haemodialysis by urea kinetic modeling (UKM), a vital method for determining the optimal dialysis dose. This study was conducted at the haemodialysis unit of the National Institute of Kidney Diseases and Urology (NIKDU), Dhaka, Bangladesh between the periods of 1st January 2012 and 30th June 2013. Purposive sampling of 120 end stage renal disease (ESRD) patients on maintenance haemodialysis (MHD) getting dialysis for at least one month through arterio-venous fistula (AVF) and at least 2 dialysis sessions per week. Out of 120 patients, 72 (60%) were male and the ratio was 1.5:1. The mean age of haemodialysis patients in this study was 51 years (range: 18-75 years). Approximately 62 (52%) patients were on an 8-hour per week haemodialysis session. Our study showed mean total clearance of urea normalized or corrected for distribution volume (Kt/V), urea reduction ratio (URR), time average concentration of urea (TACurea) and normalized protein catabolic rate (nPCR) of all study population was 1.21±0.40, 62±12, 83±26, and 1.29±0.46, respectively. In 12 hours per week haemodialysis group achieved target Kt/V >1.2 was only 26 (45%), on the other hand, in 8 hours per week haemodialysis group achieved target Kt/V >2 was only 3 (5%). Among the study population only 52 (43%) patients achieved URR >65%, 13 (11%) patients TACurea was less than 52 mg/dl and 107 (89%) patients achieved nPCR >1g/kg/day. The mean values of the URR was significantly higher for dialysis patients who achieved a Kt/V of >1.2 than for those who did not achieve a Kt/V > 1.2. To achieve haemodialysis adequacy of KDOQI 2006 recommendation needs to increase the frequency of HD that is 3 sessions per week (12 hours/week) and needs to give more attention to other factors that increase urea clearance. To improve patient management with end-stage kidney disease, needs of continuous research to enhance our understanding of haemodialysis adequacy and its dose calculation.Jalalabad Med J 2025; 22 (1): 17-22.